Applications of synthetic light-driven microbial consortia for biochemicals production. (May 2022) - Gao, Hao; Manishimwe, Clarisse; Yang, Lu; Wang, Hanxiao; Jiang, Yujia; Jiang, Wankui; Zhang, Wenming; Xin, Fengxue; Jiang, Min
Highlights: Synthetic light-driven microbial consortia for biochemicals production from carbon dioxide (CO2 ). Space-efficient synthetic light-driven microbial consortia in hydrogel system for improving the stability of microbial consortia. Perspectives on orderly distribution of synthetic light-driven microbial consortia associated with 3D printing technology. Abstract: Synthetic microbial consortia provide a versatile and efficient platform for biochemicals production through the labor division. Especially, microbial communities composed of phototrophs and heterotrophs offer a promising alternative, as they can directly convert carbon dioxide (CO2 ) into chemicals. Within this system, photoautotrophic microbes can convert CO2 into organic carbon for microbial growth and metabolites synthesis by the heterotrophic partners. In return, heterotrophs can provide additional CO2 to support the growth of photoautotrophic microbes. However, the unmatched growing conditions, low stability and production efficiency of synthetic microbial consortia hinder their further applications. Thus, design and construction of mutualistic and stable synthetic light-driven microbial consortia are urgently needed. In this review, the progress of synthetic light-driven microbial consortia for chemicals production was comprehensively summarized. In addition, space-efficient synthetic light-driven microbial consortia in hydrogel system were reviewed. Perspectives on orderly distribution of light-driven microbial consortia associated with 3D printing technology in biomanufacturing were also addressed.